Respostas
respondido por:
2
f (x)=3x-8, substituimos o x pelos números que obtem o resultado da função.
a)f (3)=3 (3)-8
f (3)=9-8
f (3)= 1
b)f (0)=3 (0)-8
f (0)=0-8
f (0)= -8
c)f (5)=3 (5)-8
f (5)=15-8
f (5)= 7
d)f (3)-f (5)=
f (3)=1 -f(5)=7
1-7= -6
a)f (3)=3 (3)-8
f (3)=9-8
f (3)= 1
b)f (0)=3 (0)-8
f (0)=0-8
f (0)= -8
c)f (5)=3 (5)-8
f (5)=15-8
f (5)= 7
d)f (3)-f (5)=
f (3)=1 -f(5)=7
1-7= -6
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás